(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Gibberella zeae, Ascomycetes, Bangladesh Â DOI: 10.3329/bjpt.v15i2.1755 Â Bangladesh J. Plant Taxon. 15(2): 163-165, 2008 (December)